Le people dans la presse illustrée belge des années 1950 - Laurence Mundschau (Communication)
The author believes she has found the first signs of celebrity news in the illustrated sections of two now defunct French-language Belgian dailies (Le Patriote illustré and Le Soir illustré). Though there were some indications of celebrity news in the main sections of these mid-twentieth century dailies, the slippage from information to celebrity news is most evident in their illustrated supplements. This journalistic « experiment » coincided with an era of social experiments (1950-65) and it chose the crowned heads of Europe as its main testing ground.